Endividamento por empréstimos consignados de docentes da educação básica da rede pública estadual em Macapá/AP (2003 a 2016) - (:unkn) unknown (Brasil)
Theme of this research is the teaching indebtedness. The general objective of the study is to analyze the indebtedness of teachers of basic education of the State Public Network in Macapá to demonstrate how the logic of capital expansion has contributed to this process, in the period 2003-2016. The specific objectives are: 1) to contextualize the crisis of capitalism in the 1970s and its developments in the process of State Reform, globalization, financialization and the redefinition of capital and its influence on access to credit and the indebtedness of workers in Brazil; 2) to discuss teacher remuneration and (de) valorization of salaries, as well as their consequences in the indebtedness of payroll loans of teachers of basic education of the State Public Network of Amapá; 3) to analyze the main causes and consequences the indebtedness of the teachers of the State Public Net in Macapá for consigned loans. The research was carried out from a quali-quantitative research, having as method the dialectical historical materialism. The inferences and interpretation of the collected data were made through Content Analysis. The research had a bibliographic survey of productions that deal with the subject of the study and with the application of questionnaire with structured questions, constituted with closed and open questions, applied with 100 teachers of Basic Education, of the State Public Network in the city of Macapá. The results of the research show that the crisis of capitalism that began in the 1970s, which demanded the Reform of the State and made possible the globalization of capital and the hegemony of financial capital, for all sectors of society, provoked the expansion of access to credit to throughout the country. In the state of Amapá this process was deepened with teachers of the basic education of the state public network from the regulation of the payroll loan, which led to the growth of indebtedness among these workers, impacting directly on the lives of these education professionals, who are compromising the increasing payment of loan installments, refinancing, renegotiation and banking portability, subordinating to Banks and financial institutions a significant part of the present and future income of teachers for a long term as a constituent element of the logic of capital expansion in the phase of predominance of financial capital
Keywords: Endividamento financeiro; Crédito consignado; Professores - Salários - Amapá; CNPQ::CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CNPQ::CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DOS RECURSOS HUMANOS; POLÍTICAS EDUCACIONAIS; EDUCAÇÃO, POLÍTICAS E CULTURAS